Exploring the Causal Relationship Between Brand Attributes and Brand Equity: Key Insights from Havas' Meaningful Brands Study - Rosa, Cláudia Fonseca (2025)
In an increasingly complex and consumer-driven environment, understanding how brands create and sustain value is a priority. This study investigates the bidirectional causal relationship between brand equity and brand perception attributes (functional, personal, and collective), using data from the Havas Meaningful Brands Study 2023 (Portugal). Through regression analysis, propensity score matching, and clustering, the study finds that perceived brand attributes strongly influence brand equity, particularly functional attributes (ATT = 1.94), followed by personal (ATT = 1.73) and collective (ATT = 1.33). In the reverse direction, brand equity also improves attribute perception, though to a lesser extent (e.g., ATT on functional = 1.42). Segment-level analysis confirms this pattern across three consumer clusters with different profiles. These findings demonstrate the reciprocal role of perception and equity in shaping brand value and offer actionable insights for adjusting brand strategies to specific consumer segments and dimensions.